Pharmacokinetics of levodopa/benserazide versus levodopa/carbidopa in healthy subjects and patients with Parkinson's disease. Issue 2 (8th December 2014) - Iwaki, Hirotaka; Nishikawa, Noriko; Nagai, Masahiro; Tsujii, Tomoaki; Yabe, Hayato; Kubo, Madoka; Ieiri, Ichiro; Nomoto, Masahiro
Abstract: Background: There are two formulations of levodopa in Japan and a few other countries, levodopa/benserazide 100/25 mg and levodopa/carbidopa 100/10 mg, which have been generally regarded as interchangeable in Parkinson's disease treatment. Aim: We investigated the pharmacokinetics of levodopa in the two kinds of levodopa/decarboxylase inhibitor (benserazide or carbidopa) formulations to study their equivalence. Methods: Population pharmacokinetic analysis was carried out using levodopa data from the healthy subject study and, additionally, for 70 plasma concentration data points from Parkinson's disease patients receiving either levodopa/decarboxylase inhibitor combination in clinical practice. Results: In healthy subjects, the mean ± standard deviation plasma levodopa maximum observed plasma concentration and area under the plasma concentration time curve from time 0 to 3 h (512 ± 139 vs 392 ± 49 μmolh/L, P  < 0.05) were significantly higher after levodopa/benserazide compared with levodopa/carbidopa. Levodopa time to maximum observed plasma concentration and plasma elimination half‐life were not significantly different when comparing the respective formations. Levodopa pharmacokinetic parameters were the same between the Parkinson's disease patients and healthy subjects, except for levodopa apparent clearance, which was approximately two‐thirds lower in Parkinson's disease patients compared with healthy subjects for both levodopa/decarboxylase inhibitor combinations, which might result in higher levodopa area under the curve in patients with Parkinson's disease than in healthy volunteers. Conclusion: Levodopa pharmacokinetics differ after administration of levodopa/benserazide and levodopa/carbidopa. This information cold be useful for adjustment of medication in Parkinson's disease patients, especially with motor complications.